2022
DOI: 10.55730/1300-0144.5523
|View full text |Cite
|
Sign up to set email alerts
|

Can surfactants affect mortality and morbidity in term infants with respiratory failure?

Abstract: Background/aim We aimed to discuss term infants who are given surfactant due to respiratory disorder according to the underlying etiology, the dose of surfactant administration, and the need for repeated surfactant administration. Materials and methods In this retrospective study infants hospitalized in the 4th level neonatal intensive care unit during January 2019 and December 2021 and administered surfactant due to respiratory distress were included. Term infants give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Kitsommart et al conducted a study in Canada and reported that TTN had a frequency of 47% and RDS with a frequency of 37.3% among respiratory problems in late preterms (23). In the present study investigating the indications for surfactant administration in term infants administered surfactant because of respiratory failure, it was found that from 56 term infants who were administered surfactant, 30 term infants were administered surfactant with the diagnosis of congenital pneumonia and 22 term infants were administered surfactant with the diagnosis of TTN (24). Our recent study showed that surfactant treatment administered in the early period significantly reduces mortality in term infants with severe respiratory failure because of secondary surfactant deficiency caused by TTN and pneumonia (24).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Kitsommart et al conducted a study in Canada and reported that TTN had a frequency of 47% and RDS with a frequency of 37.3% among respiratory problems in late preterms (23). In the present study investigating the indications for surfactant administration in term infants administered surfactant because of respiratory failure, it was found that from 56 term infants who were administered surfactant, 30 term infants were administered surfactant with the diagnosis of congenital pneumonia and 22 term infants were administered surfactant with the diagnosis of TTN (24). Our recent study showed that surfactant treatment administered in the early period significantly reduces mortality in term infants with severe respiratory failure because of secondary surfactant deficiency caused by TTN and pneumonia (24).…”
Section: Discussionmentioning
confidence: 55%
“…In the present study investigating the indications for surfactant administration in term infants administered surfactant because of respiratory failure, it was found that from 56 term infants who were administered surfactant, 30 term infants were administered surfactant with the diagnosis of congenital pneumonia and 22 term infants were administered surfactant with the diagnosis of TTN (24). Our recent study showed that surfactant treatment administered in the early period significantly reduces mortality in term infants with severe respiratory failure because of secondary surfactant deficiency caused by TTN and pneumonia (24). In the present study, when the diagnoses of the infants included in the study were examined, it was found that 74 (35.1%) cases were diagnosed with TTN, 120 cases (56.9%) with the diagnosis of RDS, and 17 cases (8.1%) with the diagnosis of pneumonia in the NICU.…”
Section: Discussionmentioning
confidence: 73%
“…Surfactant therapy was employed in 38.5% of our patients, of whom 61.9% and 32.6% had RDS and MAS, respectively. While the role of surfactant therapy in RDS is well-established [ 34 , 38 ], its use for the treatment of MAS has only recently gained clinical attention. Our findings corroborated with this, and demonstrated a considerably increased use of surfactant therapy for MAS compared to the previous data (1.8%) [ 2 ].…”
Section: Discussionmentioning
confidence: 99%